Altcoins - Anna Wisniewska (Institute of Economic Research (IER), 2016)
The aim of this article is to present altcoins that seem to be most promising. The author has made an attempt at answering the questions about the reasons for their creation and if any of them is strong enough to undermine Bitcoin's position among virtual currencies. In order to find the answers there have been used the literature on the subject as well as available internet sources since the Internet is the environment in which cryptocurrencies and their makers function. The research demonstrates that among over 600 existing cryptocurrencies there exists a group of quite interesting projects. These projects has not always been targeted at creation of a new cryptocurrency: some of them have been aimed at implementing the technology used by Bitcoin in other spheres of human activity, e.g. to collect data. There have been presented three Polish cryptocurrencies, whose history shows how uncertain it is to achieve success at the market of virtual currencies even if a created cryptocurrency is believed to be well-prepared to debut. The more we get to know about the way in which altcoins function, the more we will be able to predict if it is just a passing fad or the beginning of the new age of online payments.
Keywords: E42; E49; E51; 330; cryptocurrencies; polish cryptocurrencies; ethereum; litecoin